Wpływ kompetencji obywatelskich na poziom konsolidacji demokracji w Polsce - Karnowska, Danuta (Political Preferences, 2012)
The civil competences may have a great influence on the level of the democracy con- solidation. They are a mark of knowledge about the democracy, understanding the democ- racy mechanisms and also the trust to its institutions. This way of understanding the civil competences (especially for the participating kind of political culture) seem to be not enough developed in Poland, what is proved by the results of carried out and shown research. Also the idea of the necessity of the occurrence of civil competences, understood as the compul- sion for the participating kind of political culture to work, might be exaggerated, because not always the knowledge about the democracy and its mechanisms and its institutions, must be connected with the civil activity.